Third-Party Data Leaks and Dark Patterns in Finnish Political Websites - Puhtila, Panu; Heino, Timi; Rauti, Sampsa (United States, 2025)
In the modern digital age, political parties extensively use websites as platforms for communication, engagement, and fundraising. It is important to ensure that personal data is safe when visiting these websites. For example, if pages visited by the user or search terms they used leak to third parties, this data, connected to identifying information such as IP addresses, may give clues about political affiliation. In this paper, we conduct a survey on the data leaks to third parties happening in Finnish political websites. In total, we surveyed 26 websites (main website, party chairperson's website, and e-shop/donation website of each party), and our results indicate that 19 of the 26 analyzed websites leak potentially sensitive personal data to third parties, most often to Google and Meta. Furthermore, there were leaks of personal data on all surveyed party websites, implying data leaks happen across the entire political spectrum. There is an urgent need for better data protection measures on political websites. The implications of political opinions potentially leaking to third parties can be serious, jeopardizing individuals' autonomy and democratic rights.
CompSysTech '24: Proceedings of the International Conference on Computer Systems and Technologies 2024